2015
DOI: 10.2989/16085914.2015.1077777
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land use on water quality in the Likangala catchment, southern Malawi

Abstract: Safe drinking water, good sanitation and hygiene are important for good health, human survival and development. However, human activities have affected water quality in many river catchments worldwide. Hellar-Kihampa et al. (2013) concluded that the Pangani River, Tanzania, had the worst water quality in the Moshi, Arusha and Kilimanjaro region, with the highest levels of Na + , K + , Mg 2+ , HCO 3 − and F − , the presence of these contaminants being as a result of human activities. Industrial water pollution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 15 publications
3
21
0
3
Order By: Relevance
“…Ammonium-N and Nitrate-N naturally occur in water bodies as a result of the breakdown of organic and inorganic matter in water, excretion from biota and reduction of atmospheric nitrogen by microorganisms [52,53]. However, the application of fertiliser in the irrigated rice and vegetable farms downstream could explain the relatively high level of nutrients at these particular sites [5,10,54]. Decomposition of nitrogen-containing organic compounds such as plants and crops residuals is another potential source of contamination in the area, which could explain lower mean DO values downstream irrigation.…”
Section: Physical-chemical Properties Of Watermentioning
confidence: 99%
“…Ammonium-N and Nitrate-N naturally occur in water bodies as a result of the breakdown of organic and inorganic matter in water, excretion from biota and reduction of atmospheric nitrogen by microorganisms [52,53]. However, the application of fertiliser in the irrigated rice and vegetable farms downstream could explain the relatively high level of nutrients at these particular sites [5,10,54]. Decomposition of nitrogen-containing organic compounds such as plants and crops residuals is another potential source of contamination in the area, which could explain lower mean DO values downstream irrigation.…”
Section: Physical-chemical Properties Of Watermentioning
confidence: 99%
“…The three parameters (TS, TDS, and TSS) to a greater extent evaluate the quality of a drinking water, and their violation limits the aesthetic value of the water by increasing its turbidity which in a way becomes a public health issue (Mendie 2005;Ayeni et al 2006). Some studies have indicated high turbidity in urban areas (Pullanikkatil et al 2015) and in areas where sewage is discharged into waterways (Mendie 2005). Furthermore, the high values of TS and TDS across the landuse could be attributed to various sociocultural factors such as indecent disposal of household water into water channels, excessive use of fertilizers from farming activities on floodplains and unchecked effluents discharged directly into water bodies.…”
Section: Physical Parameters Of Surface Water Quality Across Landuse mentioning
confidence: 99%
“…The studied river flows into a reservoir downstream; hence, the values as observed across the three landuse types are way beyond the permissible limit. Anthropogenic activities are the main contributors of excessive PO 4 into river channels; sewage discharge, runoff from agricultural sites, and the release of detergent during domestic washing especially along river channel sections are common practices (Saksena et al 2008;Pullanikkatil et al 2015). The load contribution of detergents raises the level of phosphate in water channels due to the weight of inorganic condensed phosphates (Usharani et al 2010).…”
Section: Chemical Parameters Of Surface Water Across Landuse Typesmentioning
confidence: 99%
See 2 more Smart Citations